Efficacy of Zingiber Officinale (ZO) in The Treatment of Lead Acetate-induced Hepatopathy in Rabbits: An Ultrastructural Assessment of Sub-acute Trial. - Mohammed Abdulabbas Hasan (College of Pharmacy University of Baghdad, 2024)
Lead acetate (Pb) is a hazardous heavy metal that is well-known to impair the functions of bodily systems and organs. This present study identifies the histopathological alterations that Pb toxicity causes in the liver of rabbits as well as the efficacy of ginger (Zingiber Officinale, ZO) in mitigating its negative effects. As ZO is a rich source of several antioxidants, this present study examines its ability to decrease Pb toxicity in test animals. A total of 30 rabbits were randomly divided into three groups (n = 10). The Control group was only fed distilled water, the Negative group was only fed a 2% Pb solution, while the Treated group was fed a 2% Pb solution as well as 100 mg of ZO extract per kilogram of body weight daily. Lead acetate (Pb) was found to significantly alter the histopathology of rabbit livers by increasing inflammation, fibrosis, vacuolation, and degeneration; significantly decreasing plasma superoxide dismutase (SOD) and catalase (CAT) enzymatic activities; and increasing plasma malondialdehyde (MDA) concentrations. Furthermore, ZO extract not only significantly decreases the negative hepatic impacts of Pb but also prevents Pb-induced hepatopathy.